2007
DOI: 10.1507/endocrj.k07-007
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ghrelin Concentrations in Different Clinical Stages of Diabetic Complications and Glycemic Control in Japanese Diabetics

Abstract: Abstract. Ghrelin is an acylated 28-amino-acid peptide that stimulates food intake, GH secretion, and gastric motility. Experimental studies have suggested that ghrelin plays roles in glucose homeostasis, atherosclerosis, and microangiopathy. We investigated possible involvement of ghrelin in micro-and macro-vascular diabetic complications and glycemic control in diabetic patients. Fasting and postprandial plasma ghrelin concentrations after a test meal were measured in 108 and 61 Japanese diabetic patients, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
2
27
2
Order By: Relevance
“…The percentage inhibition of plasma DPP-4 activity 3 days after teneligliptin administration was 68.8 ± 23.8 %. Plasma ghrelin and des-acyl ghrelin levels at 30 to 180 min after the meal fell significantly from the baseline as described previously [19] in both before and after the teneligliptin treatment. Both plasma ghrelin and des-acyl ghrelin levels, as well as the AUCs for both compounds, were unaltered by teneligliptin treatment (Fig.…”
Section: Gastrointestinal Hormonessupporting
confidence: 81%
“…The percentage inhibition of plasma DPP-4 activity 3 days after teneligliptin administration was 68.8 ± 23.8 %. Plasma ghrelin and des-acyl ghrelin levels at 30 to 180 min after the meal fell significantly from the baseline as described previously [19] in both before and after the teneligliptin treatment. Both plasma ghrelin and des-acyl ghrelin levels, as well as the AUCs for both compounds, were unaltered by teneligliptin treatment (Fig.…”
Section: Gastrointestinal Hormonessupporting
confidence: 81%
“…Plasma ghrelin levels increase upon fasting [3,5,6] and insulin-induced hypoglycemia [6], and decrease in response to oral or intravenous administration of glucose [5,7]. Plasma ghrelin level also exhibits a diurnal pattern with preprandial increases and postprandial decreases [5].…”
mentioning
confidence: 99%
“…Plasma ghrelin level also exhibits a diurnal pattern with preprandial increases and postprandial decreases [5]. Fasting plasma ghrelin level elevates in anorexia nervosa [8] and cachexia [9], and reduces in obesity [7,10].…”
mentioning
confidence: 99%
“…Therefore, the stomach may play an important role in the regulation of appetite and food intake via neurohormonal links. Lately Ueno et al showed no significant postprandial decrease in total ghrelin levels at 30 and 60 min after meal was detected in diabetic patients with autonomic neuropathy which gave a definition of CV R-R [37]. However, the active form of ghrelin could be much more useful in determining its physiological and pathophysiological role than the total form.…”
Section: Discussionmentioning
confidence: 99%